Potential of the bioeconomy in Visegrad countries: An input-output approach. (March 2022) - Lazorcakova, Ema; Dries, Liesbeth; Peerlings, Jack; Pokrivcak, Jan
Abstract: The EU has placed high priority on the expansion of the bioeconomy with the aim to reduce the use of non-renewable resources, to mitigate climate change, and to develop prospering local economies. However, only few Member States have defined quantitative economic or environmental targets for the bioeconomy in their policy strategies as measurement of the bioeconomy is not straightforward. This study uses an input-output analysis to quantify economic as well as environmental indicators for measuring the bioeconomy in the Visegrad countries (Slovakia, Czech Republic, Poland and Hungary). The current and the potential size of the bioeconomy are derived based on scenarios of minimum, medium and maximum association of partially bio-based goods with the bioeconomy. Our results suggest that currently the bioeconomy contributes 13% to the value of economic output, 10% to value added, 15% to total employment, and 20% to emissions of greenhouse gases in the Visegrad region (with a variation of 8 percentage points among individual countries). There is still potential for a transition towards a bioeconomy, especially in the production of textiles and wearing apparel, chemical products, pharmaceutical products, plastics, furniture, and energy where fossil-based inputs could be substituted by bio-based resources. Highlights: Measuring the bioeconomy is not unified in the literature. An input-output model was applied to measure the bioeconomy. Comparable and replicable results were obtained for economic and environmental indicators of the bioeconomy in Visegrad countries (Slovakia, Czechia, Poland, and Hungary). This study helps policy makers to formulate quantitative objectives in bioeconomy strategies.